How to Write Better Essays - Greetham, Bryan (New York Palgrave Macmillan, 2008)
This book takes the reader carefully through each stage of essay writing from interpretation of the question, to the research, planning, writing and revision. Readers are shown how to improve not just study skills like note taking, reading, organization and writing, but their thinking skills too. The reader will learn how to analyze difficult concepts, criticize and evaluate arguments, use evidence, and develop more of their own ideas. This book gives clear practical advice, with a troubleshooting section that deals with a range of common problems.